Faktor-Faktor Yang Menghambat Perlindungan Konsumen terhadap Pengguna Barang Thrift Fasion dipasar Andalas Kota Gorontalo - Mayanti Abdullah; Weny A Dungga; Sri Nanang Meiske Kamba (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to find out about the phenomenon of legal protection for consumers using thrift fashion goods in the Andalas market, Gorontalo City and the factors that hinder consumer protection for users of thrift fashion goods in the Andalas market, Gorontalo City. This research uses empirical legal research methods which are carried out by collecting data through observation and interviews. The results of this research indicate that Consumer Protection is regulated in Law no. 8 of 1999 which is a replacement for Law no. 3 of 1989 concerning Telecommunications. The consumer protection law itself regulates the rights and obligations of consumers, including producers, who act to meet consumer needs and ensure the realization of legal protection for the benefit of others. In essence, consumer protection is the consumer's own right, including the activities and movements of the sales industry which are currently being widely discussed and highlighted, especially the buying and selling of imported second-hand clothing, known as thrifting, namely the activity of shopping for used goods such as clothes and other types, whose prices are very high. cheaper, as well as factors that hinder the provision of this protection and make it not work as it should. In the city of Gorontalo itself, there are problems in providing consumer protection for the sale of imported second-hand clothing, namely; strong desire on the part of sellers and buyers, law enforcement is limited to socialization and appeals without confiscation and sanctions, and lack of public awareness.